Keragaman Benthos pada Budidaya Rajungan (Portunus pelagicus) di Tambak Percobaan Maranak, Balai Riset Perikanan Budidaya Air Payau Maros Sulawesi Selatan - A. Marsambauana Pirzan; Suharyanto Suharyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
A study has been conducted in Maranak Pond Station of Research Institute for Coastal Aquaculture, Maros South Sulawesi. The objective of this study was to analyse the benthos diversity on the swimming crab (Portunus pelagicus) culture in the brackishwater pond. Sampling of benthos was conducted each month for four times. Benthos samples were obtained from 9 ponds. Pipe (pvc) in diameter of 2 cm was used to collect benthos then preserved in 10% of formalin solution. Microscopically identification of benthos was conducted until genus and counting cell method was used to calculate their population density. Research results showed that benthos composition were 32 genera of phytoplankton and 15 genera of zooplankton. Varies benthos density at the range of 954 – 23,850 ind. / cm2 and genus at the range of 2 – 14 genera. Gut content of swimming crab were 6 genera of phytoplankton, Copepod nauplii and unknown organism. Benthos diversity indices was classified moderately stable in ponds 2 – 6 and 8 - 9 while in pond 1 and 7 were not stable. Evenness indices of benthos in ponds 3 - 8 were relatively more normal of distribution than ponds 1, 2 and 9. Dominance indices of ponds 3 - 9 relatively better than ponds 1 and 2.